Effect of buoyancy force on an unsteady thin film flow of Al2O3/water nanofluid over an inclined stretching sheet - Ishak, Anuar; Alabdulhadi, Sumayyah; Abu Bakar, Sakhinah; Waini, Iskandar; Ahmed, Sameh E. (MDPI, 2023)
The present study looks at the heat transfer and the unsteady thin film flow of Al2O3 water nanofluid past an inclined stretching sheet having a buoyancy force effect. The boundary value problem solver (bvp4c) package in Matlab is utilized in solving the converted set of ordinary differential equations (ODEs). The multi-shape Al2O3 nanoparticles’ impact with respect to the flow as well as heat transfer characteristics are studied and visually displayed for certain governing parameter values, which include the mixed convection, inclination angle, magnetic, slip, and Biot number. Thus, the skin friction coefficient and the local Nusselt number are also determined. Here, the platelet shape of Al2O3 nanoparticles possesses a high heat transfer and flow rate based on the outcomes. In addition, increasing the slip and magnetic parameters improves the temperature, whereas increasing the buoyancy and inclination angle parameters has reverse effects. The results also show that increasing the unsteadiness parameter and the magnetic parameter reduces the film thickness.